Implementasi Model Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Menentukan Ide Pokok Teks pada Siswa Kelas V SDIT Al Hidayah Islamic School Tahun Ajaran 2025/2026 - Umam Hudaya (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aims to improve the ability of fifth-grade students at SDIT Al Hidayah to identify the main idea of a text using the Problem-Based Learning (PBL) model. The study employed the Classroom Action Research (CAR) method and was conducted through several stages: planning, action implementation, observation, and reflection. The subjects of the study were 55 students. The results indicate that the implementation of the problem-based learning model improved students' ability to identify the main idea of a text. In the initial stage (pre-cycle), the class average score was 69.98, and the learning mastery rate was 47.27% (26 students scored below 75). Following the implementation of the problem-based learning model in the first cycle, the average score rose to 70.95 and the mastery rate reached 43.64% (24 students achieved a score of 75); however, the success indicators had not yet been met. Instructional improvements in Cycle II—achieved by strengthening learning stages, providing guidance and prompting questions, and using more contextual texts—resulted in better student outcomes. The class average score increased to 82.14, with a mastery rate of 78.18% (43 students achieved a score of 75). Student learning activity also improved, rising from 63.33% in the first cycle to 86.67% in the second cycle. Based on these findings, the implementation of the problem-based learning model is proven to significantly improve the ability of fifth-grade students at SDIT Al Hidayah to identify the main idea of a text during the 2025/2026 academic year